Proving the suitability of magnetoelectric stimuli for tissue engineering applications - Ribeiro, C. (2016)
A novel approach for tissue engineering applications based on the use of magnetoelectric materials is presented. This work proves that magnetoelectric Terfenol-D/poly(vinylidene fluoride-co-trifluoroethylene) composites are able to provide mechanical and electrical stimuli to MC3T3-E1 pre-osteoblast cells and that those stimuli can be remotely triggered by an applied magnetic field. Cell proliferation is enhanced up to 25% when cells are cultured under mechanical (up to 110 ppm) and electrical stimulation (up to 0.115 mV), showing that magnetoelectric cell stimulation is a novel and suitable approach for tissue engineering allowing magnetic, mechanical and electrical stimuli.